Kebahagiaan Menurut Syeikh Ibnu Atha’illah as-Sakandari - Ade Anang Suhada; Muliadi Muliadi; Dodo Widarda (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
The hustle and bustle of the modern era, marked by an easy life, is relatively only able to provide physical pleasure, but is unable to provide physical and spiritual happiness. The phenomenon of life that is not balanced with this level of happiness, causes a void. The purpose of this study was to determine the meaning and ways of obtaining happiness according to Syeikh Ibnu Atha’illah as-Sakandari, as well as its relevance to human life in the modern era. This research is a qualitative research that uses a library research approach. The analytical method used is a content analysis technique. The conclusion of this study, shows that the happiness referred to by Syeikh Ibnu Atha’illah as-Sakandari divided happiness in two dimensions, namely happiness in the World and happiness in the hereafter. Happiness actually exists in human. Happiness will be realized when humans are able to optimize the potential of the mind and the potential of the heart. The path to happiness can be attained by knowing the characteristics of the wordly life and suffering and reducing pleasures. Moral perfections will lead humans to true happiness, namely meeting Allah SWT in a state of faith.